2018
DOI: 10.1186/s12881-017-0519-z
|View full text |Cite
|
Sign up to set email alerts
|

Birt-Hogg-Dubé syndrome in two Chinese families with mutations in the FLCN gene

Abstract: BackgroundBirt-Hogg-Dubé syndrome is an autosomal dominant hereditary condition caused by mutations in the folliculin-encoding gene FLCN (NM_144997). It is associated with skin lesions such as fibrofolliculoma, acrochordon and trichodiscoma; pulmonary lesions including spontaneous pneumothorax and pulmonary cysts and renal cancer.MethodsGenomic DNA was extracted from peripheral venous blood samples of the propositi and their family members. Genetic analysis was performed by whole exome sequencing and Sanger se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…1). Using the study criteria outlined above, 221 cases from 120 families with BHDS were included in the final analysis, which were reported in 20 papers (Table 1) [8][9][10][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. In 2008, the first 10 families with spontaneous pneumothorax and positive FLCN mutations in the Chinese population were described by a research team at Nanjing University [8].…”
Section: Demographic Datamentioning
confidence: 99%
“…1). Using the study criteria outlined above, 221 cases from 120 families with BHDS were included in the final analysis, which were reported in 20 papers (Table 1) [8][9][10][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. In 2008, the first 10 families with spontaneous pneumothorax and positive FLCN mutations in the Chinese population were described by a research team at Nanjing University [8].…”
Section: Demographic Datamentioning
confidence: 99%
“…The second condition found to be segregating within the family is BHDS. BHDS is caused by pathogenic variants in FLCN and is inherited in an autosomal dominant manner [5, 11]. FLCN encodes folliculin, a tumor suppressor protein expressed in a variety of tissues, including the skin, distal nephron of the kidney, and type 1 pneumocytes of the lung [11].…”
Section: Discussionmentioning
confidence: 99%
“…OPMD is tested for by looking for pathogenic variants in PAPBPN1, defined as an expansion of a (GCN)10 repeat in the first exon to (GCN)12–17 repeats [4]. BHDS is tested for by looking for mutations in the FLCN gene, several of which have been described [5].…”
Section: Clinical Phenotype and Genotypementioning
confidence: 99%
“…In addition, no studies have revealed its role in tumors. However, the same family protein FLCN has been studied in breast cancer, kidney cancer and cervical cancer ( Zheng et al, 2017 ; Hou et al, 2018 ; Sattler et al, 2018 ). In view of this, our studies in gastric cancer have shown that DENND1A exerts GEF action during the activation of Rab35 stimulated by EGF, and through its interaction with Grb2, it can regionally recruit activated Rab35 and then promote the migration of tumor cells.…”
Section: Discussionmentioning
confidence: 99%